Light Transit-Konzepte zur Modernisierung des ÖPNVs. Das Beispiel der innerstädtischen Cross River Tram in Greater London. - Albanèse, Luke; Gather, Matthias; Schneider, Martin (Deutscher Verkehrs-Verl., 2006)
In den vergangenen Jahren ist die Londoner Verkehrspolitik vor allem durch die Einführung der City Maut (Congestion Charge) bekannt geworden. Nicht weniger interessant ist aber die umfassende Modernisierung des städtischen ÖPNVs, die aus diesen Einnahmen finanziert werden soll. Neben umfangreichen Investitionen in die regionalen Eisenbahnen und einer Modernisierung der Busflotte gibt es auch ehrgeizige Straßenbahnprojekte, von denen exemplarisch die Cross River Tram in der Londoner Innenstadt ausführlicher vorgestellt wird. difu

With the introduction of the congestion charge London has already taken over a leading role compared to other large world cities, which is nowadays taken as a best-practice example for inner city road pricing. Should many or all of the new ambitious public transport plans be introduced, London might be a good worldwide best practice example again: this time on how to convert a badly underfinanced, ailing public transport system into a world class public transport system. Especially the inner city light rail projects like cross river tram should be an excellent measure, on how to gain a large number of new passengers with a comparatively small financial investment. Large Underground and railway projects such as Cross Rail are also important modes for a successful public transport system, but they will result in significantly higher constructional and operational costs than light rail. In case of medium patronage levels and sufficient available road space, a bus rapid transit system might also be an alternative. But this should be planned in a way that it could easily be upgraded into a tram light rail system. difu
Keywords: Öffentlicher Verkehr; Stadtverkehr; Verkehrspolitik; Nahverkehr; Regionalverkehr; ÖPNV; Straßenbahn; U-Bahn; Verkehrsplanung; Verkehrsinvestition; Maut; Verkehrsprojekt; Best Practice; Metropole